Epidemiological Study with Evaluation of Molecular and Immunologicalassay for Detection of Toxoplasma gondii in aborted women: Toxoplasma gondii in aborted women - Alkardhi, Ihsan K. A.; Masmoudi , Hatem; Muhammedand, Hayder A.; Sellami, Hayet (Cellular and Molecular Biology, 2022)
Toxoplasmosis, caused by Toxoplasma gondii, is one of the most prevalent parasite ‎illnesses in humans. Although primary infection in a pregnant woman is usually asymptomatic, it has the potential to cause significant harm to the fetus, including miscarriage. In this study, we ‎investigate the usefulness of the PCR to confirm the etiology of the abortion. A prospective ‎study in the Al-Diwaniyah maternity and pediatric teaching hospital in Iraq was conducted. The research comprised 94 aborted women. We have reported a new ‎internal primer for the nested PCR protocol to detect toxoplasmosis. In the 94-aborted ‎women, 30 samples (31.9 %) were positive by the nPCR using the G529 repeat gene and ‎qPCR using B1 gene primers. We have shown that three women carry the ‎parasite in their placentas, and at the same time, they do not carry antibodies in their blood.‎ We recommend that women should be aware of the risk of toxoplasmosis and the ‎importance of preventing measures. In addition, PCR should be done in the case of ‎abortion to enhance sensitivity even if serology is negative.